Impact Of Integrated Yoga Practice on Immune Parameters and Quality of Life of Adult People Living With HIV: Protocol for A Randomized Open-Label Trial in Chittoor, India - Kiranmayi Koni; Jayanthi Tarugu; Sirshendu Chaudhuri; Hema Kurugundla; Anusha Puthalapattu; KR John; Silpa Chintham (Medsci Publications, 2023)
Background: Yoga therapy can be a promising adjunct to antiretroviral therapy. However, evidence on the effectiveness of Yoga therapy is scanty. The proposed trial will estimate the effect of integrated yoga practice for six months on immune parameters (CD4 (cluster of differentiation 4), viral load) among adult people living with HIV (PLWH) and its cost-effectiveness from the healthcare system's perspective. Methods: In this randomized open-label parallel-group trial, 110 PLWH in stage 2 HIV, between 18 and 49 years in the intervention arm and 220 PLWH in the same stage will be recruited by block randomization. Integrated yoga practice will be given for six months in the intervention arm, and health education on yoga practice in the control arm, besides antiretroviral therapy. After six months, the difference in immune parameters, cardio-metabolic indicators and quality of life (QOL) will be assessed. Besides, an economic evaluation will be done with sensitivity analysis. If found useful, the intervention can be tested at large scale for further confirmation of the outcomes. Irrespective of the study's outcome, the results will be disseminated through peer-reviewed journals. Trial registration: CTRI/22/09/045909 dated 27/09/2022 under the Clinical Trials Registry-India version: 1.0 dated 27/09/2022